(untitled) (Res Gesta, 2020)
After the overthrow of Juan Domingo Perón in 1955, a process of “desperonización” began. That meant, among other things, the dismantling of the university regime. In such circumstances, was promulgated the Decree of "Organización de las Universidades Nacionales” and that would put an end to the restructuring of the peronist model and would conciliate the creation of universities from the private initiative. Three actors would participate in the debate that was generated during the foundation and regulation process: the governments of the “Revolución Libertadora” (1955-1958) and Dr. Arturo Frondizi (1958-1962), the Catholic Church, and the University. Due to the confessional character of the first universities to emerge, symbolic constructions would begin to intertwine the creation of private institutions with a Church project. In this context, we will analyze some of the arguments proposed in favor of the creation of the new model and how the above mentioned actors interacted during the process.